Perceived knowledge and perceptions toward biostatistics among dental and medical undergraduate students in International Islamic University Malaysia (IIUM) - Haslim, Hani Zawani; Mohamad Zin, Ain Nadzirah; Mohd Ibrahim, Mohamad Shafiq; Che Musa, Muhd Firdaus; Sayed Kamar, Syarifah Haizan (2021)
Introduction: The acknowledgement of evident-based practice (EBP) in clinical studies and practice require a thorough understanding of biostatistics among early researchers in dental or medical studies. Thus, it is vital for dental and medical undergraduates students to acquire a knowledge of biostatistics. Aim and objectives: This study in done to assess the level of perceived knowledge and perceptions regarding biostatistics among dental and medical undergraduates students in International Islamic University of Malaysia (IIUM). Material and methods: A cross-sectional study was undertaken among dental and medical undergraduates students session 2019/2020 (n=190). An online set of self-assessment questionnaires exploring students perceived knowledge and perceptions were distributed between October to December 2020. The data were analyzed in SPSS version-25 by using Mann-Whitney U Test. Results: Responses from the survey reveal that both groups have a higher level of average perceived knowledge (Dental=68%; Medical=84%) and positive perceptions (Dental=62%; Medical=60%) towards biostatistics. However, medical students have slightly or moderately higher result than undergraduates dental students in IIUM across all domains 76-93%). Conclusions: Although most of the participants had greatest knowledge and positive perceptions towards biostatistics, in this study IIUM undergraduates medical students however were found to have a slightly better perceived knowledge and perceptions than the dental students. A rigorous educational review is required on biostatistics module implemented at the IIUM dental faculty to inform future educational policy changes, thus ensuring they are in line with their medical counterpart.